Suspended Conversations The Afterlife of Memory in Photographic Albums Second Edition. - Langford, Martha (McGill-Queen's University Press, 2021)
Exhibiting a collection of photographic travelogues, memoirs, thematic collections, and family sagas compiled between 1860 and 1960 and held by the McCord Museum of Canadian History, this second edition includes a revised and expanded preface along with new photographs of the Notman albums.